Odontogenic Maxillary Cysts Post-Dental Implant: Proposal of New Radiological/Clinical Classification - Gamba, Paolo (International Journal of Innovative Research in Medical Science, 2017)
Case description - A 62 years old male presented with h/o recurrent episodes of pain and swelling in both knee joints leading to flexion deformity on left side.(Figure1A) He also had a soft tissue swelling in right thigh for last 30 years, which was nontraumatic and gradually progressive in size. On examination, a well-defined swelling of 15 x 10 cm was present over right thigh, which was compressible, nonreducible, and non-tender. (Figure2A) History of recurrent episodes of epistaxis and spontaneous gum bleeds since early childhood was also present. Laboratory investigations revealed increased clotting time with increased activated partial thromboplastin time (aPTT). Platelet count, bleeding time and prothrombin time were normal. Factor VIII levels were low (2%) suggestive of moderate haemophilia. X-ray right thigh and bilateral knees confirmed it to be case of haemophilic arthropathy with pseudotumour. (Figure1B and 2B) Hemophilic pseudotumor is a rare complication occurring in 1–2% of patients with haemophilia. [1]Repetitive bleeding into the bones and soft tissues results in pseudotumor, whereas repetitive bleeding into the joints leads to arthropathy.[2] Pseudotumours are most common in thigh, while haemophilic arthropathy classically involves knee joint. Soft-tissue pseudotumors manifest as nonspecific masses at radiography. They may demonstrate internal calcifications or ossifications. Most of the morbidity from pseudotumors is due to their compressive effect on surrounding structures including bone destruction. Haemophilic arthropathy of knee tends to be asymmetric in involvement.Changes include Juxta-articular osteoporosis, irregular appearance of the subchondral surface,multiple subchondral cysts and widening of the intercondylar notch.[3] This report describes two important musculoskeletal complications of haemophilia. Long term factor replacement is essential for treatment and surgery is required in pseudotumours which are progressively increasing and for end stage haemophilic arthropathy.